PENERAPAN PEMBELAJARAN ONLINE (DALAM JARINGAN) DI SEKOLAH DASAR - Widyangsih, Octaviany (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
Abstract: Pandemic Covid-19 made government implemented the regulation of education that learning process only conduct by distance education, thus one of the method in this programme was by online learning. The objective of this research was to digging information about the online learning process by elementary teachers. Using the descriptive qualitative method with subjects of 37 teachers in Bogor City. Data was collected by survey with 2 type of questions (open and closed questions). The results shows, that before pandemic Covid-19 the implementation of online learning in elementary schools were very low, but after pandemic the readiness of teachers regarding the goverment regulation is well accomodated even though teachers still have shortcoming with the authenticity of learning outcomes from assignments. Furthermore, teachers still cannot fully conduct evaluation by online assessment particularly to evaluate the affective and social aspects. Keywords: elementary school, instructional, online, implementation